2015
DOI: 10.1111/jzo.12229
|View full text |Cite
|
Sign up to set email alerts
|

White rhinoceros Ceratotherium simum horn development and structure: a deceptive optical illusion

Abstract: The alleged traditional medicinal properties of rhinoceros horn resulted in a dramatic escalation in rhinoceros poaching in South Africa. Despite the listing of all species of rhinoceros in the International Union for Conservation of Nature Red List of threatened animals, their numbers are still declining rapidly. Based on the assumption that rhinoceros' horn consists of a collection of hollow tubules and intertubular hollow spaces, which allow internal fluid distribution, a horn devaluation procedure through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Rhinos also dig with their horns during wallowing behaviours (Wilson et al, 2020) which act to protect the skin from parasites and aid in thermoregulation on hot days (Metrione & Eyres, 2014). However, unlike the horns of several tropical bovid species (Picard et al, 1999), rhino horns have no thermoregulatory function as they are made of keratin and lack a vascularised bony core (Boy et al, 2015). Prior to wallowing, Sumatran rhinos dig soil from the banks of pits with their horns and feet, a practise that likely acts to thicken the consistency of the mud (Van Strien, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Rhinos also dig with their horns during wallowing behaviours (Wilson et al, 2020) which act to protect the skin from parasites and aid in thermoregulation on hot days (Metrione & Eyres, 2014). However, unlike the horns of several tropical bovid species (Picard et al, 1999), rhino horns have no thermoregulatory function as they are made of keratin and lack a vascularised bony core (Boy et al, 2015). Prior to wallowing, Sumatran rhinos dig soil from the banks of pits with their horns and feet, a practise that likely acts to thicken the consistency of the mud (Van Strien, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies [22,23] showed that tubular and lamellar structures exist in the bighorn sheep horn. Flattened and cornified epithelial cells (keratinized cells) grow from dermal papilla that are arranged in concentric layers around a central medulla, forming the tubular structures [24][25][26]. Tubular structures in other keratinized tissues such as equine hooves and rhinoceros horns were identified and characterized in previous studies [24,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A rhino's horns grow continuously from a growth layer at the base of the horn (Boy et al, 2015). Although African black and white rhinos have similar intrinsic horn growth rates, irrespective of sex, the rate varies with age (Pienaar et al, 1991).…”
mentioning
confidence: 99%